Exploring methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate and varying flexible bis(imidazole)-based synthons as building blocks for the construction of diverse cadmium coordination polymers. (February 2018) - Li, Zhao-Hao; He, Sheng-Jun; Xue, Li-Ping; Wang, Xiao-Ning; Zhang, Dan-Dan; Zhao, Bang-Tun
Abstract: Three Cd(II)-based coordination polymers (CPs) with unique structures and topologies, namely, [Cd2 (L)2 (bimb)2 (H2 O)2 ]n (1 ), {[Cd(L)(bmib)0.5 (H2 O)](CH3 OH)0.5 }n (2 ) and [Cd(L)(beib)0.5 (H2 O)]n (3 ) (H2 L = methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate, bimb = 1, 4-bis(imidazol-1′-yl)butane, bmib = 1, 4-bis(2-methylimidazolyl)butane and beib = 1, 4-bis(2-ethylimidazolyl)butane) have been successfully constructed and characterized by single crystal X-ray structure determination, IR spectra, elemental analyses and powder X-ray diffractions. X-ray results showed compound1 features a new 2-nodal 5, 6-connected 3D network with a point symbol of {4 5 .5.6 3 .7}2 {4 2 .5 4 .6 9 }. Compound2 exhibits a rare 6-fold interpenetrating dia 3D network. Compound3 bears a hydrogen bonded-extended 3D supramolecular structure based upon sql layers assembled from dinuclear Cd(II) units. Thermal stability and solid photoluminescence properties of compounds1 –3 were studied. Significantly, compound1 can sense nitrobenzene through the luminescence quenching effect. Graphical abstract: Three new Cd(II)-based coordination polymers with unique structures and topologies have been successfully constructed using a new designed methyl-3-hydroxy-5-carboxy-2-thiophenecarboxylate ligand in the presence of bis(imidazole) ligands. Highlights: Three Cd(II)-based coordination polymers with unique structures and topologies were constructed. H2 L ligand with multiple potential coordination sites remains unexplored. Compound1 can sense nitrobenzene through the luminescence quenching effect.